Introduction - Dena, Christy; Keogh, Brendan (Transactions of the Digital Games Research Association, 2017)
On 2 April 2016, the DiGRA Australia chapter held its inaugural regional symposium in Brisbane, Queensland. The goal of this symposium, in part, was to highlight and identify the broader scholarship happening on games beyond the usual geographic scope of Australia's other east-coast capital cities, and beyond the usual conceptual frames of game studies. The theme of 'wayfinding' was chosen to both guide paper submissions and the exploratory philosophy of the symposium itself. This journal issue presents a selection of extended and reworked papers initially presented at the symposium, representing authors from a range of disciplinary backgrounds, from across Australia and overseas.